Effects of Salinity on Leaf and Grain Protein in Some Genotypes of Oat (Avena sativa L.) - Kumar and Alka Singh, Ashok Kumar, Sanjay Agarwal, Pramod (Recent Research in Science and Technology, 2010)
The protein content in oat, like in the other cereal species, is much influenced by the environmental conditions as well as by the variety. This investigation was carried out on the effect of salinity on protein content in leaves and grains of four genotypes of oat (JHO-822, JHO-851, Kent and UPO-94). The plants were irrigated with different saline waters (3, 6, 7.2, 10, 12 and 14 dSm-1) in the field. Protein in leaf was analyzed at 90 days after sowing. Cv. JHO-822 and JHO-851 contained higher leaf protein at 3 and 6 dSm-1 but lower at 7.2 to 14 dSm-1. Kent and UPO-94 registered an increase in leaf protein only at 3 dSm-1 but declined at all salinities. Grain protein of cultivars of oat also registered significant enhancement at 3 dSm-1 but significant reductions at other salinities. The higher protein content in leaves and grains in cv. JHO-822 may be due to higher photosynthetic rate of plants due to higher total leaf area.